Próba utworzenia katedry historii Bizancjum na Uniwersytecie Jana Kazimierza we Lwowie. Przyczynek do dziejów bizantynistyki w Polsce - Królczyk, Krzysztof (Studia Europaea Gnesnensia, 2020)
This text discusses the attempts to create a chair of history of Byzantium at the Jan Kazimierz University in Lwów (today Lviv in Ukraine), in late 1933. After the end of the First World War, no chairs of Byzantine history existed at the universities in Poland. However, when Kazimierz Zakrzewski, a young scholar and expert on the history of late antiquity and Byzantium, came to Lwów, the idea to establish such a chair at the local university was conceived. Professor Edmund Bulanda drafted a special paper in which he justified the need to create a chair of Byzantine history at the Jan Kazimierz University in Lwów. The Council of the Faculty of the Humanities decided to apply to the Ministry of Religious Affairs and Public Education, with a request to have such a department created. Unfortunately, central authorities responded in the negative. Two years later, however, a chair of Byzantine history was created at the University in Warsaw and it was assumed by the very same Kazimierz Zakrzewski. In Lwów (from 1945 officially Lviv) itself, the chair of Byzantine studies was created at the beginning of the 21st century, in the realities of the new Ukrainian state.